THE EFFECT OF GREENWASHING ON BRAND EQUITY AND GREEN PURCHASE INTENTION AT GARNIER IN JAKARTA - Rahayu, Herawati; Saktiana, Galuh Mira (International Journal of Application on Economics and Business, 2023)
Climate change and global warming are causing various natural disasters. One of the causes is packaging waste from consumer-packaged goods products (in the form of food, drinks, and dairy products such as soap, cosmetics, etc.) which are difficult to decompose. Public awareness is needed to preserve the environment, one of which is by using environmentally friendly products such as Garnier through the "green beauty" movement. The purpose of this research is to examine how greenwashing affects brand equity, including brand trust and brand association with Garnier products, and to examine the effect of brand equity on green purchase intention. The quantitative and descriptive method was used by distributing questionnaires via Google form to 128 respondents in Jakarta using the Structural Equation Model (SEM) analysis tool to test the hypothesis. The results showed that the five hypotheses proved significant and acceptable, namely, green brand equity has a positive effect on green purchase intention, brand credibility, and brand associations are also proven to have a positive effect on green brand equity, while greenwashing has a negative effect on brand credibility and brand associations, especially in consumer-packaged goods. Thus, Garnier is expected not to do greenwashing so that it can maintain consumer trust in Garnier products and continue to improve campaign programs that invite people to care about the environment, one of which is by buying environmentally friendly packaging products such as Garnier.